The Potential of Zakat in Poverty Alleviation to Achieve SDG 2: Zero Hunger - Bhupinder Singh; Saquib Ahmed; Ashima Jain (Asy-Syari'ah, 2025)
Abstract: Zakat is part of the five pillars of Islam which is considered significant in poverty alleviation in addition to the promotion of social justice and economic redistribution. Therefore, this study aims to examine the role of zakat in alleviating poverty in order to achieve Sustainable Development Goal (SDG) 2: Zero Hunger with a specific focus on food security. The trend is associated with the importance of a robust social safety net that meets the basic sustenance needs of all members of society. This shows the possibility of zakat serving as a continuous mechanism of wealth redistribution from an Islamic perspective. A literature review with a case study method was used to explore successful zakat practices in Muslim-majority countries to effectively alleviate hunger, support small-scale farmers, and enhance social welfare. It was concluded that zakat could be effectively integrated into contemporary economic and social policies to play a meaningful role in improving food security and promoting sustainable poverty alleviation. The process could further serve as a contribution to the achievement of SDG 2.